THE OPTIMIZATION OF TRANSPORTATION, ITS ECONOMIC PRODUCT AND MARKETS - A. Kurbatova (Вестник университета)
The article gives an improved definition of economic product of transport, covers the peculiarities of transport markets and proposes the strategy of traffic division among transport modes in modern conditions. The importance of government regulation of transport markets and the need to improve the infobase of the state accounting and control are emphasized. It also defines the main scientific problems of transport sector.